Association of rhinovirus with exacerbations in young children affected by cystic fibrosis: Preliminary data. Issue 8 (14th March 2017) - Stelzer‐Braid, Sacha; Liu, Nancy; Doumit, Michael; D'Cunha, Russell; Belessis, Yvonne; Jaffe, Adam; Rawlinson, William D.
Abstract : Rhinovirus (RV) is a common respiratory viral infection linked to worsening of chronic respiratory diseases including cystic fibrosis (CF) and asthma. RV was tested by RT‐PCR in samples ( n  = 465) collected from the upper (nasal swab, oropharyngeal suction, and sputum) and lower (bronchoalveolar washings) respiratory tract of 110 children with CF. Air samples ( n  = 52) collected from the operating theatres and outpatient clinics were tested for RV. RV was found in 43% of children <5 years suffering an exacerbation, and 12% of older children (5‐17 years). RV particles were detected in the air of clinic rooms. Detection of RV is important in better understanding viral infections in patients with CF.